PUJA CARU PADA MASYARAKAT JAWA KUNA - Santiko, Hariani (Paramita: Historical Studies Journal, 2011)
The offering known as caru or macaru is still done in Bali. This macaru in Bali is actually blood sacrifice offered to the lords of the demonds (bebutan or butabala) before the Balinese doing a special ritual for instance the Nyepi ceremony. The most important caru is called Ã¢â¬Åcaru mancasanakÃ¢â¬Â, they sacrifice animals and other ingredients. The word caru is known in Old-Javanese inscriptions and Old-Javanese/Middle-Javanese texts among others are the Adiparwa, RÃÂmÃÂyana, Sutasoma, Korawasrama, Calon Arang. However no special explanation on the meaning of the word caru and its rituals. ÃÂ Keywords: pÃ Â«jÃÂ caru, ambhÃ Â«tayajÃÂ±a, buburpÃâhan, pindapitryÃÂjÃÂ±a, kunda, homayajÃÂ±a, skul-dinyun. ÃÂ Korban yang dikenal sebagai caru atau macaru masih dilakukan di Bali. Hal ini macaru di Bali sebenarnya darah pengorbanan yang ditawarkan kepada raja butha (bebutan atau butabala) sebelum Bali melakukan ritual khusus misalnya upacara Nyepi. Yang paling penting adalah caru disebut